Anti-flowing-water bi-component rapid-hardening micro-fracture grouting material for mine and preparation method and application thereof
Through the use of anti-moving water two-component quick-setting micro-crack grouting material, the reaction mechanism of magnesium phosphate cement and the composite stabilizing and compacting effect of fly ash are used to solve the problems of rapid hardening and high compressive strength of grouting materials in the existing technology. It achieves rapid sealing and high-strength reinforcement of micro-cracks in mines, and has good water resistance and fluidity.
Patent Information
- Application Number
- CN202411410265.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-24
AI Technical Summary
The existing mine grouting materials have shortcomings in rapid hardening and high compressive strength, and are susceptible to water flow erosion in water-flow erosion, and have poor fluidity and diffusion.
Using anti -water dual -component semaphinosome microcullet grouting materials, this material consists of composition A and group B, which can be quickly hardened through the magnesium phosphate cement reaction mechanism, and improves through the composite effect of molor coal ash and sodium siliconate. Water resistance.
It achieves rapid sealing and high-strength reinforcement of micro-cracks in mines. It has good fracture permeability, can resist underground water erosion, has high fluidity and good diffusibility, simple production process and low cost.
Smart Images

Figure CN119349975A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mine grouting construction materials, and in particular to a two-component quick-setting micro-crack grouting material for mines that resists dynamic water, and a preparation method and application thereof. Background Art
[0002] Grouting materials for mines mainly include coal mine grouting materials, grouting filling materials, cement-based grouting materials and chemical grouting materials, etc. These materials play an important role in mining projects, including preventing gas accumulation, reinforcing tunnels, filling holes, sealing closed walls, reducing spontaneous combustion, waterproofing and fire prevention, and preventing gas explosions.
[0003] CN112341136A discloses a kind of underground micro-crack grouting plugging material and grouting process for mines. The material is a common ultra-fine cement grouting material. The plugging material components include bentonite, ultra-fine cement, water glass and water. The water-solid ratio of the mass of water to the sum of the mass of bentonite and ultra-fine cement is 0.8:1-4:1, the mass ash-soil ratio of ultra-fine cement to bentonite is 1:1-1:3, and the amount of water glass added is 2%-10% of the ultra-fine cement. The maximum particle size of ultra-fine cement can generally be ≤20μm, and the minimum particle size can reach 1-2μm, with good permeability; the material source is wide and the production process is simple. However, in order to achieve rapid setting, the material generally has a high content of water glass. Excess water glass combines with silicate hydration products to produce expansive cementitious materials. The final compressive strength is generally around 1 MPa, which is too low. Water glass-stimulated silicate cement can set quickly, but it is difficult to harden quickly. The hardening time is at least more than 1 hour, and it is easily eroded by water when encountering a water-rich environment.
[0004] CN103254394A discloses a polyurethane grouting water blocking reinforcement material and a preparation method thereof, which is a common organic grouting material. The raw materials of the polyurethane grouting water blocking reinforcement material and the weight percentage of the raw materials are: polyether polyol: 50-60%; polyisocyanate: 30-40%; cross-linking agent: 1-5%; chain extender: 1-10%; catalyst: 0.1-0.2%; defoamer: 0.2-1.8%. The polyether polyol, chain extender, cross-linking agent, catalyst and defoamer after vacuum dehydration are sequentially added to the reaction cup to fully mix them and make white material. Under stirring, add black material isocyanate and continue stirring until the mixture is evenly mixed; after the solution color is mixed and the temperature rises, pour it into the mold to foam when it turns white, and prepare the sample after it is fully matured. The invention has uniform distribution, regular arrangement, few defects, and its impact fracture morphology shows brittle fracture characteristics, and the water blocking rate is more than 95%. This chemical grouting material has low viscosity, good injectability, fast reaction and can achieve rapid plugging. However, since it is a high molecular organic material, the raw material cost is high and the use cost is high; organic materials have the risk of contaminating groundwater; organic materials will age due to long-term exposure to high temperature, extrusion, and bacterial colonies; when used in coal mines, since it is an organic combustible material, there is a risk of flammability.
[0005] CN118063185A discloses a two-component magnesium phosphate cement-based anchor and a method of using the same. The anchor comprises a paste-like component A and a component B. Component A comprises dead-burned magnesium oxide, mineral admixture, modified gangue aggregate, polyethylene glycol, fiber, water reducer, cellulose, polymer glue powder and mixing water. Component B comprises phosphate, retarder, polyethylene glycol and mixing water. The preparation method of the modified gangue aggregate is as follows: the gangue aggregate is subjected to a roasting treatment, and after completion, the roasting product is crushed to obtain the modified gangue aggregate. When the components A and B are mixed, the dead-burned magnesium oxide in the component A and the phosphate in the component B constitute magnesium phosphate cement, and hydration reaction is carried out under the action of mixing water to form a high-strength, high-adhesive hydration product struvite, which can firmly bond the anchor rod to the surrounding rock, and has the characteristics of high early strength and strong anchoring force. However, the production process of this solution is complicated, the actual application cost is high, and there is no cost advantage in actual engineering application; there is secondary construction of anchor rods during construction, and the construction efficiency is low in actual application; the product of this technical solution is a paste when applied, with poor fluidity, and contains a large amount of thickening components, and has poor diffusivity. It can only block the anchor rod holes and cannot fully diffuse to achieve micro-crack grouting reinforcement.
[0006] Therefore, it is necessary to develop a new quick-setting micro-crack grouting material in this field. Summary of the invention
[0007] The purpose of the present invention is to provide a two-component quick-setting micro-crack grouting material for mines, a preparation method and an application thereof. The material is suitable for micro-crack grouting in coal mines, metal mines and other mines, has good crack permeability, can achieve quick hardening, has high strength, belongs to the category of inorganic materials, is resistant to aging and pollution-free, resists erosion and dilution of underground dynamic water during grouting, has high fluidity and good diffusivity, has a simple production process and is low in cost.
[0008] Specifically, this application provides the following technical solutions:
[0009] A two-component quick-setting micro-crack grouting material for mines with anti-dynamic water, comprising component A and component B, wherein the raw materials of component A are mixed in the following proportions by mass fraction: 58% to 86.3% of MgO; 0.5% to 1% of high-efficiency water reducing agent; 1% to 3% of retarder; 0.1% to 0.5% of quick-dissolving anti-dispersant; 10% to 35% of ceramsite sand; 0.1% to 0.5% of flexible chopped fibers; and 1% to 5% of calcium chloride;
[0010] The raw materials of component B are mixed in proportion by mass fraction as follows: phosphate 53% to 82.8%; fly ash 5% to 10%; high-efficiency water reducing agent 0.5% to 1%; retarder 1% to 3%; quick-dissolving anti-dispersant 0.1% to 0.5%; expanded clay sand 10% to 30%; flexible chopped fibers 0.1% to 0.5%; and sodium silicate 0.5% to 2%.
[0011] Wherein, the MgO is dead-burned MgO.
[0012] Wherein, the phosphate is one or both of ammonium dihydrogen phosphate and potassium dihydrogen phosphate.
[0013] Wherein, the retarder is borax or sodium tripolyphosphate.
[0014] Wherein, the high-efficiency water reducer is a polycarboxylate water reducer.
[0015] Wherein, the instant anti-dispersant is at least one of polyvinyl alcohol, xanthan gum and hydroxypropyl methylcellulose.
[0016] Wherein, the calcium chloride is industrial grade calcium chloride.
[0017] Wherein, the sodium silicate is solid sodium silicate with a modulus of 2.8-3.5.
[0018] The ceramsite sand is a light single-grain ceramsite sand with a diameter of 2-3 mm and a bulk density of 300-900 kg / m 3 The light and round particles make it have a ball effect when mixed into grouting material, which greatly increases the fluidity of the grouting material.
[0019] Wherein, the flexible chopped fibers are polypropylene fibers and / or glass fibers, with a length of 3-6 mm.
[0020] The preparation method of the anti-dynamic water two-component quick-setting micro-crack grouting material for mines of the present invention is specifically as follows:
[0021] The preparation method of component A is to first grind the heavy-burned MgO, high-efficiency water reducer, retarder, quick-dissolving anti-dispersant and calcium chloride into a mixed powder for 1 hour until the specific surface area is 4600cm 2 / g, with an average particle size of about 30μm; and then dry-mixed with expanded clay sand and flexible short-cut fibers to form the finished product.
[0022] The preparation method of component B is to first grind phosphate, fly ash, high-efficiency water reducer, retarder, quick-dissolving anti-dispersant and sodium silicate to a specific surface area of 3500cm 2 / g or more, with a median particle size of about 10μm; and then dry-mixed with expanded clay sand and flexible short-cut fibers to form a finished product.
[0023] The anti-dynamic water two-component quick-setting micro-crack grouting material for mines described in the present invention can be used for sealing micro-cracks in mines. The specific method is: when using, water is added to material A and material B according to a water-to-material ratio of 0.3 to 0.4, and stirred for more than 3 minutes to form slurry. A grouting pump is used to suck the slurry of material A and material B into a mixing tube for mixing, and then a grouting anchor is used to cooperate to inject into the grouting hole drilled in advance.
[0024] The main application principle of the anti-dynamic water two-component quick-setting micro-crack grouting material for mines of the present invention is as follows:
[0025] Reaction mechanism of magnesium phosphate cement: after heavy burned MgO and phosphate are mixed with water, soluble phosphate dissolves first; + Under the action of 2+ OH - , and react with the ions decomposed from phosphate to form a crystalline product, commonly known as struvite. This reaction is rapid, with 50% of the total reaction completed in 2 hours and 80% of the total reaction completed in 1 day. This reaction can enable the grouting material to quickly harden within 30 minutes. When magnesium phosphate cement is in a water environment for a long time, the unreacted phosphate will be dissolved first, making the solution form an acidic environment, promoting the dissolution of hydration products and residual MgO, and decomposing Mg 2+ , Plasma, these ions migrate to the surface and recrystallize to form new MAP, resulting in a decrease in the content of hydration products in the slurry. In this process, cracks and harmful pores will be generated, causing the strength of MPC to shrink. Therefore, it is necessary to compound other materials to enhance the water resistance of magnesium phosphate cement materials.
[0026] The mechanism of fly ash improving the water resistance of magnesium phosphate cement: the metal oxides inside the fly ash undergo a solidification reaction with phosphates, eliminating the negative impact of excess phosphates, reducing the precipitation and recrystallization of hydration products by consuming remaining phosphates, and filling the cracks itself, making the microstructure of magnesium phosphate cement stone more compact, improving the density of the cement stone, and improving water resistance.
[0027] Reaction mechanism of sodium silicate and calcium chloride: The reaction of sodium silicate and calcium chloride is often used for soil reinforcement, foundation treatment, and waterproofing. When used, sodium silicate is prepared into water glass and calcium chloride is prepared into a solution. When the two liquids are mixed, they react instantly to form calcium silicate gel. Since the sodium silicate solution and the calcium chloride solution are in a molecular state, the permeability is greatly enhanced compared to traditional cement-based materials. The disadvantage is that the strength is generally only a few megapascals when used alone, which is too low. However, it has obvious advantages in plugging microcracks. Molecular sodium silicate and calcium chloride can react in microcracks to form calcium silicate gel to plug the cracks, play a role in plugging and reinforcing, and reduce the continued expansion of stress when the surrounding rock is broken and cracked.
[0028] Principle of anti-seepage dynamic water erosion: General grouting materials have poor resistance to dynamic water erosion. When encountering dynamic water erosion, they are diluted by large flow of dynamic water and are washed out of the grouting anchor hole by dynamic water before they can undergo a solidification reaction. The grouting material of the present invention greatly delays the mixing of dynamic water and grouting material through the pulling and isolating effect of the anti-dispersant and the fiber, thereby gaining sufficient reaction time for the solidification reaction of the grouting material; large amounts of dynamic water seepage are generally accompanied by larger seepage cracks in the surrounding rock. To reduce the impact of dynamic water erosion, the best solution is to reduce the dynamic water flow rate. Single-grain ceramsite sand and chopped fibers can seal large cracks and greatly reduce water seepage. At the same time, single-grain ceramsite is not in the most densely packed state, and the gaps between the ceramsite reserve sufficient pores for the grouting material to pass through the net slurry, which is convenient for the grouting material to reinforce the micro-cracks.
[0029] Compared with the prior art, the anti-dynamic water two-component quick-setting micro-crack grouting material for mines and its preparation method and application have at least the following beneficial effects:
[0030] (1) The anti-dynamic water two-component quick-setting micro-crack grouting material for mines of the present invention has a fineness similar to that of commonly used micro-crack grouting materials and can be injected into micro-cracks with a width of ≤0.2 mm; the raw material price is low and the cost is controllable; the compressive strength is high; it can achieve rapid hardening and sealing, reducing the impact of water seepage from the cracks; it is safe, environmentally friendly, pollution-free, and non-flammable; and the production and construction processes are simple.
[0031] (2) The grouting material of the present invention can achieve rapid hardening like organic materials and high compressive strength like ultrafine cement grouting materials. Moreover, it has high fluidity and good diffusivity and can achieve a certain resistance to underground flowing water seepage, thus preventing the grouting material from being washed out of the anchor hole by flowing water before hardening.
[0032] (3) Components A and B in the grouting material of the present invention are mixed and ground separately, with an average particle size of 10 to 30 μm; at the same time, sodium silicate and calcium chloride at the composite molecular level react to form calcium silicate gel, so that the grouting material has good permeability to microcracks.
[0033] The following is a further description of the anti-dynamic water two-component quick-setting micro-crack grouting material for mines, its preparation method and its application in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The present invention is a flow chart of the preparation and grouting process of the anti-dynamic water two-component quick-setting micro-crack grouting material for mines.
[0035] Figure 2 Schematic diagram of the anti-dynamic water performance test device.
[0036] Figure 3 The following are the strength test results of Examples 1-3.
[0037] Figure 4 The hardening time test results of Examples 1-3 are shown.
[0038] Figure 5 Compressive strength comparison results. DETAILED DESCRIPTION
[0039] Example 1
[0040] like Figure 1 As shown, a two-component quick-setting micro-crack grouting material for mines with anti-dynamic water is composed of component A and component B.
[0041] Component A is composed of: dead-burned MgO 65%; Subote PCA-300P high-efficiency water reducer (produced by Jiangsu Subote Company) 0.6%; Subote SBT-SR (Ⅰ) retarder (produced by Jiangsu Subote Company) 1%; TD-KFS1 instant anti-dispersant (produced by Jiangsu Dejiatuoda Building Materials) 0.3%; ceramsite sand (bulk density 650kg / m 3 , water absorption rate 8.5%, barrel pressure strength 7.6MPa, Zhejiang Zhongjin Environmental Protection Co., Ltd.) 30%; PP500 flexible short fiber (Shandong Taicheng Fiber Co., Ltd.) 0.5%; calcium chloride 2.6%. During production, heavy-burned MgO, high-efficiency water reducer, retarder, instant anti-dispersant, and calcium chloride are mixed and ground for 1 hour to a specific surface area of 4600cm 2 / g, with an average particle size of about 30μm, and then dry-mixed with ceramsite sand and flexible short-cut fibers to form the finished product.
[0042] Component B is composed of: KH2PO4 59.1%; fly ash 7%; Subote PCA-300P high-efficiency water reducer (produced by Jiangsu Subote Company) 0.6%; Subote SBT-SR (Ⅰ) retarder (produced by Jiangsu Subote Company) 1%; TD-KFS1 instant anti-dispersant (produced by Jiangsu Dejiatuoda Building Materials) 0.3%; ceramsite sand (bulk density 650kg / m 3 , water absorption rate 8.5%, barrel pressure strength 7.6MPa, Zhejiang Zhongjin Environmental Protection Co., Ltd.) 30%; PP500 flexible short-cut fiber (produced by Shandong Taicheng Fiber Co., Ltd.)
[0043] 0.5%; sodium silicate (mode 1.6, Baume 40°Bé) 1.5%. During production, KH2PO4, fly ash, high-efficiency water reducer, retarder, quick-dissolving anti-dispersant and sodium silicate are mixed and ground to a specific surface area of 3500cm 2 / g or more, with a median particle size of about 10μm, and then dry-mixed with expanded clay sand and flexible short-cut fibers to form the finished product.
[0044] When in use, add water to component A and component B according to a water-to-material ratio of 0.3 and stir for more than 3 minutes to form slurry. Use a grouting pump to suck slurry A and slurry B into a mixing tube for mixing, and then use grouting anchor rods to inject into the grouting holes drilled in advance.
[0045] Example 2
[0046] like Figure 1 As shown, a two-component quick-setting micro-crack grouting material for mines with anti-dynamic water is composed of component A and component B.
[0047] Component A is: dead-burned MgO 63%; Subote PCA-300P high-efficiency water reducer (produced by Jiangsu Subote Company) 0.6%; Subote SBT-SR (Ⅰ) retarder (produced by Jiangsu Subote Company) 3%; TD-KFS1 instant anti-dispersant (produced by Jiangsu Dejiatuoda Building Materials) 0.3%; ceramsite sand (bulk density 650kg / m 3 , water absorption rate 8.5%, barrel pressure strength 7.6MPa, Zhejiang Zhongjin Environmental Protection Co., Ltd.) 30%; PP500 flexible short-cut fiber (Shandong Taicheng Fiber Co., Ltd.) 0.5%; calcium chloride 2.6%. During production, heavy-burned MgO, high-efficiency water reducer, retarder, instant anti-dispersant, and calcium chloride are mixed and ground for 1 hour to a specific surface area of 4600cm 2 / g, with an average particle size of about 30μm, and then dry-mixed with ceramsite sand and flexible short-cut fibers to form the finished product.
[0048] Component B is composed of: KH2PO4 57.1%; fly ash 7%; Subote PCA-300P high-efficiency water reducer (produced by Jiangsu Subote Company) 0.6%; Subote SBT-SR (Ⅰ) retarder (produced by Jiangsu Subote Company) 3%; TD-KFS1 instant anti-dispersant (produced by Jiangsu Dejiatuoda Building Materials) 0.3%; ceramsite sand (bulk density 650kg / m 3 , water absorption rate 8.5%, barrel pressure strength 7.6MPa, Zhejiang Zhongjin Environmental Protection Co., Ltd.) 30%; PP500 type flexible short fiber (Shandong Taicheng Fiber Co., Ltd.) 0.5%; sodium silicate (mode 1.6, Baume degree 40°Bé) 1.5%. During production, KH2PO4, fly ash, high-efficiency water reducer, retarder, quick-dissolving anti-dispersant, and sodium silicate are mixed and ground to a specific surface area of 3500cm 2 / g or more, with a median particle size of about 10μm, and then dry-mixed with expanded clay sand and flexible short-cut fibers to form the finished product.
[0049] When in use, add water to component A and component B according to a water-to-material ratio of 0.4 and stir for more than 3 minutes to form slurry. Use a grouting pump to suck slurry A and slurry B into a mixing tube for mixing, and then use grouting anchor rods to inject into the grouting holes drilled in advance.
[0050] Example 3
[0051] like Figure 1 As shown, a two-component quick-setting micro-crack grouting material for mines with anti-dynamic water is composed of component A and component B.
[0052] Component A is: dead-burned MgO 85.4%; Subote PCA-300P high-efficiency water reducer (produced by Jiangsu Subote Company) 0.6%; Subote SBT-SR (Ⅰ) retarder (produced by Jiangsu Subote Company) 1%; TD-KFS1 instant anti-dispersant (produced by Jiangsu Dejiatuoda Building Materials) 0.3%; ceramsite sand (bulk density 650kg / m 3 , water absorption rate 8.5%, barrel pressure strength 7.6MPa, Zhejiang Zhongjin Environmental Protection Co., Ltd.) 10%; PP500 flexible short fiber (Shandong Taicheng Fiber Co., Ltd.) 0.1%; calcium chloride 2.6%. During production, heavy-burned MgO, high-efficiency water reducer, retarder, instant anti-dispersant, and calcium chloride are mixed and ground for 1 hour to a specific surface area of 4600cm 2 / g, with an average particle size of about 30μm, and then dry-mixed with ceramsite sand and flexible short-cut fibers to form the finished product.
[0053] Component B is composed of: KH2PO4 79.5%; fly ash 7%; Subote PCA-300P high-efficiency water reducer (produced by Jiangsu Subote Company) 0.6%; Subote SBT-SR (Ⅰ) retarder (produced by Jiangsu Subote Company) 1%; TD-KFS1 instant anti-dispersant (produced by Jiangsu Dejiatuoda Building Materials) 0.3%; ceramsite sand (bulk density 650kg / m 3 , water absorption rate 8.5%, barrel pressure strength 7.6MPa, Zhejiang Zhongjin Environmental Protection Co., Ltd.) 10%; PP500 type flexible short fiber (Shandong Taicheng Fiber Co., Ltd.) 0.1%; sodium silicate (mode 1.6, Baume degree 40°Bé) 1.5%. During production, KH2PO4, fly ash, high-efficiency water reducer, retarder, quick-dissolving anti-dispersant, and sodium silicate are mixed and ground to a specific surface area of 3500cm 2 / g or more, with a median particle size of about 10μm, and then dry-mixed with expanded clay sand and flexible short-cut fibers to form a finished product.
[0054] When in use, add water to component A and component B according to a water-to-material ratio of 0.3 and stir for more than 3 minutes to form slurry. Use a grouting pump to suck slurry A and slurry B into a mixing tube for mixing, and then use grouting anchor rods to inject into the grouting holes drilled in advance.
[0055] (1) The grouting materials of Examples 1-3 above are marked as ZJ-1, ZJ-2, and ZJ-3, respectively. The setting time, strength, and anti-dynamic water dispersion ability of the three grouting materials after mixing are tested respectively.
[0056] The strength test is carried out using a 40×40×160mm test mold, and the test is based on GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)"; the final setting time test is based on GB / T 1346-2011 "Test method for water consumption, setting time and stability of cement standard consistency".
[0057] In order to compare the anti-dynamic water performance, a dynamic water performance test device was designed to simulate dynamic water and surrounding rock pores of different diameters, and the grouting materials of Examples 1-3 were grouted respectively. The effect of parameter changes on the performance of the grouting materials was evaluated according to the water blocking conditions and the amount of grouting materials used. Figure 2 As shown, the whole is cylindrical, with a grouting port in the center of the lower part, and water inlets and outlets on both sides of the upper part. From top to bottom, the device is equipped with Φ2mm perforated plates, Φ5mm perforated plates, Φ10mm perforated plates, and Φ20mm perforated plates. During the experiment, tap water was introduced into the device, and the tap water filled the device to block the grouting port. After the water flowed out of the tap water outlet normally, the grouting material was prepared and mixed, and grouting was started from the grouting port until the grouting port was blocked by the grouting material and no obvious tap water flowed out of the grouting port, which was the qualified standard.
[0058] The experimental results are as follows:
[0059] The strength test results of Example 1 (ZJ-1), Example 2 (ZJ-2), and Example 3 (ZJ-3) are as follows: Figure 3 The hardening time test results are shown in Figure 4 It can be seen that the increase of retarder and water-to-cement ratio will reduce the strength at each age and significantly delay the setting time.
[0060] The comparison of the anti-dynamic water capabilities of Examples 1-3 is shown in Table 1.
[0061] Table 1 Comparison of dynamic water resistance test of different embodiments
[0062]
[0063] It can be seen from Table 1 that too long setting time and too little ceramsite aggregate and fiber will weaken the grouting material's ability to resist dynamic water and increase the cost of the plugging material.
[0064] (2) With regard to the performance of the two-component quick-setting micro-crack grouting material of the present invention, the grouting material of Example 1 was selected and compared with the common organic polymer grouting material Marisan (produced by Shandong Zhongheng Mining Machinery Co., Ltd.) and ultrafine cement grouting material (produced by Guangzhou Xinyue Concrete New Materials Co., Ltd., "Xinyue Concrete" brand) on the market. The test results are as follows: Figure 5 .
[0065] Depend on Figure 5 It can be seen that the two-component rapid-setting micro-crack grouting material of the present invention can achieve rapid hardening and early strength in comparison with organic polymer grouting materials, and can also achieve final high strength in comparison with traditional ultrafine cement grouting materials.
[0066] Table 2 Comparison of hardening time, microcrack permeability and flammability
[0067]
[0068] As can be seen from Table 2, the grouting material of the present invention can achieve rapid hardening, avoiding the problem of traditional cement-based materials that they solidify for a long time without hardening; the organic polymer material is at the molecular level and has natural micro-cracks and high permeability; the micro-crack permeability of the grouting material of the present invention is between that of fine cement and organic polyurethane materials; at the same time, the grouting material of the present invention is also an inorganic non-metallic material, which is safe and fireproof.
[0069] (3) Comparison of the ability of different types of grouting materials to resist the influence of dynamic water
[0070] In a coal mine in Zaozhuang, Shandong, there is serious water seepage in a certain section of the underground main tunnel within a length of 50m. After drilling the grouting anchor holes, the average water flow rate of the anchor holes reaches 0.1L / S. After research and analysis, it is found that the surrounding rock in this section has large cracks and rich water content. In order to maintain the normal function of the tunnel, grouting and water blocking reinforcement are required. In order to compare the anti-dynamic water capacity of several common grouting materials with the grouting material of the present invention, the following grouting materials are selected for field drilling and grouting. For the consistency and accuracy of the test plan, 3 anchor holes are drilled for each grouting material for grouting. The grouting holes are all located in this 50m length of water seepage area. After the grouting is completed, the grouting and water blocking effect is observed.
[0071] Four kinds of grouting materials were selected: grouting material A (grouting material in Example 1), grouting material B (ordinary cement-based grouting material), grouting material C (fast-hardening cement-based grouting material), and grouting material D (polyurethane-based grouting material).
[0072] Grouting material B is mainly composed of ordinary Portland cement (more than 94%), water reducing agent (less than 1%), and early strength agent (less than 5%). When using, just add water and stir.
[0073] The main components of grouting material C are: Material A: sulphoaluminate cement, water reducing agent, Material B: lime, gypsum, steel slag, slag, water reducing agent, accelerator; when in use, components A and B are added with water and stirred separately, and then mixed for grouting.
[0074] Grouting material D is mainly composed of: Component A: polyisocyanate (one or more of toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI) and polymethylene polyphenyl polyisocyanate (PAPI)) Component B: polyol, catalyst (within 1.6%), chain extender (within 0.6%) and foam stabilizer (within 1%). When used, materials A and B (in liquid state) are mixed at the grouting port, and chemical reaction and expansion occur immediately.
[0075] The comparison of test results is shown in Table 3.
[0076] Table 3 Comparison of grouting material's ability to resist dynamic water
[0077]
[0078] It can be seen from the above experimental results that the main component of the grouting material of the present invention is inorganic non-metallic material, the cost is controllable, it is a non-combustible material, safe, environmentally friendly and pollution-free. The grouting material can be quickly hardened in a short time, and has a certain water blocking effect for the grouting dynamic water situation, which solves the problem of traditional cement-based materials solidifying for a long time without hardening. At the same time, the phosphate cement hardening mechanism and the composite stabilization and densification effect of fly ash are utilized to improve the density, so that the water resistance of the grouting material is greatly improved, and the strength retention rate is improved. The particle diameter of this material is small and it is compounded with molecular-level sodium silicate and calcium chloride reactions. Compared with traditional ultrafine cement materials, it has higher permeability; and through the composite effect of single-grained ceramsite sand, flexible chopped fibers, and anti-dispersants, a certain ability to resist seepage dynamic water erosion is achieved.
[0079] The embodiments described above are merely descriptions of preferred implementation modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A two-component quick-setting micro-crack grouting material for mines, characterized in that: It includes component A and component B, wherein the raw materials of component A are mixed in the following proportions by mass: MgO 58% to 86.3%; high-efficiency water reducing agent 0.5% to 1%; retarder 1% to 3%; quick-dissolving anti-dispersant 0.1% to 0.5%; ceramsite sand 10% to 35%; flexible short-cut fiber 0.1% to 0.5%; calcium chloride 1% to 5%; The raw materials of component B are mixed in proportion by mass fraction as follows: phosphate 53% to 82.8%; fly ash 5% to 10%; high-efficiency water reducing agent 0.5% to 1%; retarder 1% to 3%; quick-dissolving anti-dispersant 0.1% to 0.5%; expanded clay sand 10% to 30%; flexible chopped fibers 0.1% to 0.5%; and sodium silicate 0.5% to 2%.
2. The anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claim 1 is characterized in that: The MgO is dead-burned MgO; the phosphate is one or both of diammonium phosphate and dipotassium phosphate.
3. The anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claim 1, characterized in that: The retarder is borax or sodium tripolyphosphate; the high-efficiency water reducer is a polycarboxylate water reducer.
4. The anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claim 1, characterized in that: The instant anti-dispersant is at least one of polyvinyl alcohol, xanthan gum and hydroxypropyl methylcellulose.
5. The anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claim 1, characterized in that: The sodium silicate is solid sodium silicate with a modulus of 2.8-3.
5.
6. The anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claim 1, characterized in that: The ceramsite sand is a light single-grain ceramsite sand with a diameter of 2-3 mm; the bulk density of the ceramsite sand is 300-900 kg / m 3 .
7. The anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claim 1, characterized in that: The flexible chopped fibers are polypropylene fibers and / or glass fibers, and have a length of 3-6 mm.
8. The method for preparing the anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claims 1-7, characterized in that: The preparation method of component A is to first grind the heavy-burned MgO, high-efficiency water reducer, retarder, quick-dissolving anti-dispersant and calcium chloride into a mixed powder for 1 hour until the specific surface area is 4600cm 2 / g, average particle size 30μm; then dry-mixed with ceramsite sand and flexible short-cut fibers to obtain the finished product.
9. The method for preparing the anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claim 8, characterized in that: The preparation method of component B is to first grind phosphate, fly ash, high-efficiency water reducer, retarder, quick-dissolving anti-dispersant and sodium silicate to a specific surface area of 3500cm 2 / g or more, with a median particle size of 10μm; and then dry-mixed with expanded clay sand and flexible short-cut fibers to form a finished product.
10. Application of the anti-dynamic water two-component quick-setting micro-crack grouting material for mines according to claims 1-7 in plugging micro-cracks in mines, characterized in that: When in use, add water to material A and material B according to a water-to-material ratio of 0.3 to 0.4 and stir for more than 3 minutes to form slurry. Use a grouting pump to suck material A and material B slurry into a mixing tube for mixing, and then use grouting anchor rods to inject into the grouting holes drilled in advance.
Citation Information
Patent Citations
Polyurethane grouting water-plugging reinforcement material and preparation method thereof
CN103254394A
Mine underground micro-crack grouting plugging material and pulping and grouting process
CN112341136A